2018
DOI: 10.3390/nu10091316
|View full text |Cite
|
Sign up to set email alerts
|

Senior Secondary School Food Literacy Education: Importance, Challenges, and Ways of Improving

Abstract: Food literacy education at senior secondary school can provide both immediate and long-term benefits for adolescents. The exploration of multiple stakeholder groups’ opinions regarding the importance, roles, and challenges of school food literacy education, and their suggestions for its improvement, will help the design and execution of future food literacy-related curricula and programmes. This study explored a broad range of Australian and international food, health, and education professionals’ opinions reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
(79 reference statements)
0
7
0
Order By: Relevance
“… 11 Home economic teachers in Australia reported that high schools are well positioned to improve adolescents’ food safety knowledge 15 and this is reflected in recent research that food, health and education professionals in Australia are highly supportive of senior secondary school food literacy education. 16 Further research with parents in the USA reinforced views that food safety education needed to be taught and reinforced in school and at home. 17 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Home economic teachers in Australia reported that high schools are well positioned to improve adolescents’ food safety knowledge 15 and this is reflected in recent research that food, health and education professionals in Australia are highly supportive of senior secondary school food literacy education. 16 Further research with parents in the USA reinforced views that food safety education needed to be taught and reinforced in school and at home. 17 …”
Section: Discussionmentioning
confidence: 99%
“…15 Our study reports that educators feel they have a role to play in educating young people on food hygiene and food safety topics, and this is echoed in findings in Sweden. 11,15,16 Educators in Sweden believed that food safety is an important part of HCS. 11 Home economic teachers in Australia reported that high schools are well positioned to improve adolescents' food safety knowledge 15 and this is reflected in recent research that food, health and education professionals in Australia are highly supportive of senior secondary school food literacy education.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In application, FL studies examine the interaction between FL and home economics [ 59 , 60 , 61 , 62 ] or measure FL. The latter, small but growing body of literature measures FL levels to determine health outcomes and diet quality in adults [ 63 , 64 , 65 , 66 ] adolescents [ 56 , 57 , 67 , 68 , 69 , 70 ] and children [ 71 , 72 , 73 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is renewed interest in secondary school food and nutrition education in many countries because of the impact that adolescent food behaviours have on their cognitive performance, diet quality, and health trajectories (Colatruglio and Slater, 2014; Engler-Stringer, 2010; Lichtenstein and Ludwig, 2010; Nanayakkara et al , 2018; Pendergast and Dewhurst, 2012; Rathi et al , 2018). Secondary school food and nutrition curricula offer an accessible means to communicate healthy eating messages with widespread reach among adolescents and their families (Burton and Worsley, 2012; Lloyd et al , 2012; Pérez-Rodrigo et al , 2001).…”
Section: Introductionmentioning
confidence: 99%